'Race', youth sport, physical activity and health: global perspectives: edited by Symeon Dagkas, Laura Azzarito and Kevin Hylton, London, Routledge, 2019, 212 pp., 252 AUD, ISBN: 978-0-8153-5822-0 (hbk)/ISBN: 978-1-351-112294-8 (ebk). Issue 7 (1st September 2020) - Whatman, Susan
ABSTRACT: ' Race', youth sport, physical activity and health: Global Perspectives is part of the Routledge book series on Critical Perspectives on Equality and Social Justice in Sport and Leisure. This book fulfils its ambition to interrogate 'race' and reveal processes of systemic racialization in physical activity and youth sport contexts and educational sites for health and physical education. The Editors, Symeon Dagkas, Laura Azzarito and Kevin Hylton, have drawn together an impressive international collection of contributors who define, conceptualize and empirically demonstrate the manifestations of 'race' as a social-political construction and its debilitating effects in physical settings. Drawing upon a range of school, community sport and college/university contexts, the book offers teachers of health and physical education, sport coaches, researchers and academics a searing critique of White hegemony in their places of work and can provide that difficult but important step in becoming a more inclusive profession.